Connecting Canadians: Investigations in Community Informatics - Andrew Clement, Michael Gurstein, Graham Longford, Marita Moll, and Leslie Regan Shade (Athabasca University Press, 2012)
Connecting Canadians represents the work of the Community Research Alliance for Community Innovation and Networking (CRACIN), the largest national and international research effort to examine the burgeoning field of community informatics, a cross-disciplinary approach to the mobilization of information and communications technologies (ICT) for community change. Funded for four years by the SSHRC's Initiative for the New Economy, CRACIN systematically studied a wide variety of Canadian community ICT initiatives, bringing perspectives from sociology, computer science, critical theory, women's studies, library and information sciences, and management studies to bear on networking technologies. A comprehensive thematic account of this in-depth research, Connecting Canadians will be an essential resource for NGOs, governments, the private sector, and multilateral agencies across the globe.